(untitled) (Journal of the College of Basic Education, 2022)
The quantitative standard approach represents an important turning point in the history of the development of psychology in general. Psychological tests and measures of all kinds in particular, which are the result of this approach. The factor analysis approach has a significant role in the development of the mental measurement movement. Spearman concluded At the beginning of the current century, the general intelligence factor (the general factor) was investigated by factor analysis of the results of a group of The tests were shown. Thurston rejected Spearman’s theory in the general factor, which includes that the results of